Studi Ontologi, Epistemologi, dan Aksiologi Teks Fiksi pada Buku Teks Bahasa Indonesia Kelas VII: Study of Ontology, Epistemology, and Axiology of Fiction Texts in Indonesian Language Textbooks for Class VII - Amelia, Dinda; Suryaman, Maman; Suroso, Suroso (Jurnal Filsafat Indonesia, 2025)
This study aims to examine the ontology, epistemology, and axiology aspects of fiction texts in Indonesian language textbooks for grade VII of the Merdeka Curriculum. The ontology aspect focuses on the existence and nature of the fictional text, while the epistemology aspect is a way to explore the deep knowledge formed and conveyed through the fictional text. This research uses a content analysis method with a qualitative descriptive approach. The sample used is the Indonesian textbook for Grade VII published by the Ministry of Education and Culture of the Republic of Indonesia. The data were collected through careful reading and recording of the fictional texts contained in the textbooks, and analyzed using Miles and Huberman's theory, namely data reduction, data presentation, and conclusion drawing. The results of this study show that there are seven fictional or literary texts in the grade VII Indonesian textbook, namely: poem titled 'Tembang Kinanthi', fantasy story titled 'Bola-Bola Waktu', two comics titled 'Kue-kue Mao' and 'Keberanian Emas', pantun, gurindam, and magical mantra. Based on the analysis, the fantasy texts reflect, shape, and convey knowledge and values to learners. The results of this study provide an in-depth understanding of the role and contribution of fictional texts in order to show how these texts enrich literary literacy, shape character, and instill moral and ethical values in students. This research shows that fictional texts in Indonesian language textbooks for grade VII of Merdeka Curriculum not only function as literary learning materials, but also as an effective medium to convey important knowledge and values to learners. The implication of this research underscores the importance of selecting and composing fiction texts to support meaningful and holistic learning.